Consuming wellness : Millennials’ reflections on wellness consumption and related identity construction - Savolahti, Anniina (My University, 2018)
Recently wellness has become one of the consumption trends of the 21st century. Consumers’ increasing interest in health and holistic well-being have created a growing demand for wellness products and services. The demand for these commodities and services is driven by consumer segments, which have expressed a need for these health-improving products. So far in the academic journals only few studies have explored wellness consumption defined by consumers. Since consumer research has long established a connection between self-identity and consumption behavior, exploring wellness consumption within the concept of self-identity is a noteworthy addition to the consumer behavior research. The theoretical framework of this research paper consisted of the concepts of wellness, wellness consumption and self-identity in the context of consumption. Various research streams within wellness were closely examined. The chosen method for this thesis was qualitative in nature, and the purpose was to study how Millennial consumers understand wellness consumption and how self-identity is constructed by the studied group of consumers. For the empirical part of the research, semi-structured interviews were conducted using an interview guide. The respondents consisted of ten female Millennials between the ages of 23–33 living in the Helsinki area. Finally, answers to the research questions were presented by comparing empirical findings to the existing theory within wellness consumption and identity construction. The findings revealed that wellness is in fact multifaceted subject and wellness as a term has not been clearly or distinctly defined or is highly dependent on the context or individual in question, therefore leading to various interpretations. According to this group of consumers, nutrition, physical exercise, wellness products as well as experience economy are closely linked to wellness consumption. Millennials’ interest in personal well-being and increasing self-awareness in health issues supports the notion of wellness as a noteworthy research area in consumption behavior. Also, the presence of multiple identities in connection to wellness consumption was clearly indicated.
Keywords: wellness, well-being, wellness consumption, self-identity, self